2020
DOI: 10.54083/resbio.2.1.2020.08-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pheromone Traps for the Management of Pod Borer, Helicoverpa armigera (Hubner) in Redgram [Cajanus cajan (L.) Millsp.] Ecosystem

Abstract: The present study entitled "Evaluation of pheromone traps for the management of pod borer, Helicoverpa armigera (Hubner) in Redgram [Cajanus cajan (L.) Millsp.] ecosystem" was carried out to study the influence of trap height on catches of H. armigera in redgram ecosystem during kharif 2017 at experimental farm of NPRC, Vamban and farmer's field at Vadakaddu.Funnel traps were more effective compared to delta traps and green funnel traps placed at the level of crop canopy (96.0 moths / 5 traps) and one foot bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These seasonal differences in captures may be either related to the seasonal changes of the growth of the cotton plants and their fruiting organs or to the population fluctuations of the insect. Priyanka et al [33] found that traps placed at canopy level in pigeon-pea cultivation gathered a higher number of male adults of H. armigera than the traps that were placed one and two feet above and below the canopy level. The seasonality of the captures of H. armigera at traps placed at different heights has been also reported by Ujjan et al [29], who observed the highest catches at chickpea crops in traps placed at 6 feet (183 cm) during the crop season and at 4 feet (122 cm) after harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These seasonal differences in captures may be either related to the seasonal changes of the growth of the cotton plants and their fruiting organs or to the population fluctuations of the insect. Priyanka et al [33] found that traps placed at canopy level in pigeon-pea cultivation gathered a higher number of male adults of H. armigera than the traps that were placed one and two feet above and below the canopy level. The seasonality of the captures of H. armigera at traps placed at different heights has been also reported by Ujjan et al [29], who observed the highest catches at chickpea crops in traps placed at 6 feet (183 cm) during the crop season and at 4 feet (122 cm) after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the characteristics of the traps, other factors that affect the capture rate in pheromone traps are the trap placement, the pheromone source and the trapping location [24,26,27,30]. There are a number of studies on the impact of the height at which the trap is placed on the number of captures of several insect species [27,[29][30][31][32][33]. Kavallieratos et al [27] reported that trap height had no influence on the adult male captures of the olive moth, Prays oleae (Bernard) (Lepidoptera: Yponomeutidae), in olive orchards.…”
Section: Introductionmentioning
confidence: 99%
“…India stands as a prominent global hub for pulse cultivation, contributing to approximately 35-36% of the total pulse-growing area and 27-28% of pulse crop production worldwide (Swathi et al, 2018). In India, an impressive 12-14 million tons of pulses are produced annually, utilizing approximately 22-24 million ha of agricultural land for this purpose (Cherif © 2023 Priyanka et al, 2023 mobility, rapid reproduction rate and the ability to enter diapause are key factors that contribute to its status as a major pest of pulses (Fitt, 1989;Lekha Priyanka et al, 2020). This pest initiates its infestation during the seedling stage and subsequently consumes flowers and developing seeds within pods until the crop reaches maturity (Lekha Priyanka et al, 2020;Mandal and Roy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intensive and indiscriminate application of these pesticides can result in detrimental consequences for the ecosystem. These include the development of resistance to insecticides, environmental degradation, negative impacts on beneficial plant and animal species, and the resurgence of secondary pests (Lekha Priyanka et al, 2020;Phokela et al, 1990). Managing pod borers with chemical insecticides is complicated due to the cryptic behavior of the larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation